The cerebellum in emotions and psychopathology - Schutter, Dennis J. L. G. (Abingdon, Oxon ; New York, NY : Routledge, 2021)
This groundbreaking volume examines the complex role of the cerebellum in emotional regulation and disorders that are insufficiently understood, subverting the widely held belief that the cerebellum is solely involved in balance and motor functions. Beginning with the evolution of the cerebellum toward a structure dedicated to homeostatic regulation and socio-emotional behavior, the book examines the growing body of evidence supporting the importance of the cerebellum in emotions, cognition, and psychopathology. Going on to discuss the implications of cerebellar abnormalities, Schutter analyzes groundbreaking research and explores how cerebellar abnormalities are associated with disruption in associative learning in anxiety, the pathophysiology of depression and cognitive regulation, the synchronization of information processing in schizophrenia, the aberrant connectivity patterns in autism spectrum disorders, and explosive forms of aggressive behavior. Collating pioneering research on the multifaceted role of the cerebellum, this book will be essential reading for students and researchers of neurology and psychopathology.
1. Evolution and basic anatomy of the cerebellum -- 2. The cerebellum link to motivation and emotion -- 3. Disorders of fear and anxiety: a big role for the little brain? -- 4. The cerebellar basis of mood disorders -- 5. Cerebellum and affective dysmetria in schizophrenia -- 6. The socio-emotional cerebellum in autism spectrum disorder -- 7. Emotionally explosive minds: a cerebellum-oriented theory on reactive aggression
OCLC-licensed vendor bibliographic record.
Keywords: Emotions and cognition; Cerebellum; Emotions; Psychology, Pathological; PSYCHOLOGY / General; PSYCHOLOGY / Cognitive Psychology; PSYCHOLOGY / Emotions